ANALISIS PENGARUH BAURAN PEMASARAN TERHADAP KEPUTUSAN, KEPUASAN DAN LOYALITAS KONSUMEN DALAM PEMBELIAN ROTI CERIA DI JEMBER - Haris Hermawan* (Universitas Muhammadiyah Jember, 2015)
Roti Ceria is sweet bakery products sold in Jember district. On business development, management will expand the sales area in each district. The Company choose the low end segment which is realized at low cost, and determine product positioning in the market sweet bread alone. Management of Roti Ceria has conducted the marketing mix of product strategy, pricing, distribution, and promotion, but do not know the effectiveness, problems for the expansion of sales areas need to be scientifically conducted studies to measure the marketing mix and its influence on the decision, satisfaction and customer loyalty as a Roti Ceria ideas for follow-up. This study shows the overall hypothesis is acceptable, in this case there is a significant influence of the product, distribution, and promotion of the decision; there is a significant influence on satisfaction of products and pricing; there is a significant influence on decision satisfaction, and there is the influence significant decisions and satisfaction to loyalty.